ALG3‐CDG: Report of two siblings with antenatal features carrying homozygous p.Gly96Arg mutation. (30th June 2015) - Lepais, Laureline; Cheillan, David; Frachon, Sophie Collardeau; Hays, Stéphane; Matthijs, Gert; Panagiotakaki, Eleni; Abel, Carine; Edery, Patrick; Rossi, Massimiliano
<x xml:space="preserve">Abstract</x> Congenital disorders of glycosylation (CDG) are a group of inborn errors of metabolism presenting with heterogeneous multisystemic clinical manifestations. To date, more than 60 different types of CDG have been reported. ALG3‐CDG is very rare, with only nine patients described so far. We report two affected siblings presenting prenatally with skeletal abnormalities associated with dysmorphic features, cerebellar vermis hypoplasia, corpus callosum agenesis, hepatic fibrosis and poor prognosis. This is the first detailed report of an affected fetus including clinical, radiographic and pathological findings. The patients showed some clinical features previously unreported in ALG3‐CDG, such as bone dysplasia, cataract, corneal opacities, and pons hypoplasia. Both patients were homozygous for the previously unreported p.Gly96Arg mutation of the ALG3 gene. One patient showed chondrodysplasia punctata (CDP), which has not been previously reported in CDG. An exhaustive genetic and metabolic assessment, performed in order to rule out other possible causes of CDP, showed abnormally raised levels of anti‐nuclear antibodies in the mother who, nevertheless, did not show any clinical sign of autoimmune disease during a 7 years follow‐up. We speculate that the observed CDP may be explained by the maternal anti‐nuclear antibodies; alternatively, a possible link to the underlying metabolic disorder cannot be ruled out. In conclusion, we report the clinical, pathological, biochemical and molecular characterization of two further patients affected by ALG3‐CDG, expanding the phenotypic spectrum of this very rare disease. © 2015 Wiley Periodicals, Inc.